STUDI KRITIS AKAD PEMBIAYAAN MUSYÂRAKAH PADA PERBANKAN SYARI'AH - Agus Arwani (Jurnal Hukum Islam, 2010)
Risk represents an unavoidable consequence in an investment based on financing. In an partnership agreement, an upcoming and potential risk must be calculated and anticipated in order to make risk reduce. Risk financing could be diminished through good management and restricted screening in partnership and projects. Transparency as one of Good Corporate Governance (GCG) principles play a very important role in a company. The importance of GCG deals with the company apprehensiveness about exposure information that enable his competitor to know his strategy and endanger his business continuity. Transparency on banking industries refers to profit sharing obtained and reported by customers to the bank.